PENGARUH TIPE PENGASUHAN, LINGKUNGAN SEKOLAH, DAN PERAN TEMAN SEBAYA TERHADAP KECERDASAN EMOSIONAL REMAJA - Woro Priatini; Melly Latifah; Suprihatin Guhardja (Jurnal Ilmu Keluarga dan Konsumen, 2008)
Emotional intelligent as one aspect of human resources is very important to achieve successful living of individual and society. It is a learned behavior that transferred to individual from social environment from early childhood to old ages through socialization within family and out side the family. Facts show that in Indonesia especially in urban area many adolescent high school boys and girls have limited emotional intelligent. The objective of the study is to analyze the effect of parenting, school environment, and role of peer group to adolescent emotional intelligent. The study was carried out in Bogor Municipality. Two hundred samples consisted of 100 students enrolled in senior high school and their parents, especially mother, respectively were drawn using stratified random sampling method with school performance quality as stratification criteria. Data were collected through interviews and self reporting. Descriptive statistics and multiple regressions were used to analyze the data. Results showed that father education attainment and age of mother affect emotional parenting type. Emotional parenting type, school discipline, emotional learning offered in school curriculum, and role of peer group as social comparison learning affect adolescent emotional intelligent significantly